Chinese new villages : a case study of Val D'or and Jawi - Jeremiah, Elizabeth N (Universiti sains malaysia, 1974)
This chapter will trace the phenomeno of how immigrant labourers from China were scattered throughout the countryside of Peninsular Malaya. It will touch on the role of these Chinese in the national framework and how they became ’’problem squatters", and why they had to be resettled.